Should Law Improve Morality? - Green, L (2013)
Lawyers and philosophers have long debated whether law should enforce social morality. This paper explores whether law should improve social morality. It explains how this might be possible, and what sort of obstacles, factual and moral, there are to doing so. It concludes with an example: our law should attempt to improve our social morality of sexual conduct. © 2013 Springer Science+Business Media Dordrecht.